The Effect Of Corporate Social Responsibility, Earnings Management And Company Size On Tax Agresivity (Empirical Study On Lq45 Index Companies Listed On The Indonesia Stock Exchange In 2013 - 2017) - Zulifah Susanty; Anggun Putri Romadhina (Indonesian Development of Economics and Administration Journal, 2022)
This study aims to examine the effect of Corporate Social Responsibility, Earnings Management and Company Size on Tax Aggressiveness. The population in this study were LQ45 Index Companies listed on the Indonesia Stock Exchange in 2013 – 2017. The sampling technique used in this study was purposive sampling and 11 (eleven) companies were obtained with a five-year research period to obtain 55 (fifty five) unit sample. Data analysis used in this study used descriptive statistical tests, classical assumption tests, and hypothesis testing. This research is a type of quantitative research. The data used is secondary data. The analytical method used is a hypothesis with the help of SPSS Version 24 software. Based on the results of the Hypothesis Test with a significant level of 5%, the results of this study conclude: (1) Corporate Social Responsibility has no significant effect on tax aggression. (2) Earnings Management has no significant effect on Tax Aggressiveness. (3) Company size has a significant effect on tax aggressiveness. 0.006. Future researchers are expected to add other variables outside of this research model, in order to enrich knowledge, especially in the field of taxation